2015
DOI: 10.1177/0146167214566188
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Focus in Predictions About Others

Abstract: Based on social projection research, four studies investigated whether people rely on their own regulatory focus when making predictions about others. Chronic (Study 1) and induced (Study 2) regulatory focus shaped estimations of others' strategic promotion or prevention inclinations and choices between enriched (fitting promotion) and impoverished options (fitting prevention). Providing indirect process evidence via boundary conditions, participants only relied on their induced regulatory focus in predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 85 publications
2
14
0
Order By: Relevance
“…Second, previous research on regulatory fit found a similar asymmetry as we did, with fit effects emerging only for promotion focus/approach orientation (e.g., Fayant, Muller, Nurra, Alexopoulos, & Palluel‐Germain, ; Nussinson et al, ; Righetti et al, ; see also Woltin & Yzerbyt, ). This has been attributed to the greater focus on similarities rather than differences under promotion focus/approach orientation (Förster, ; Förster, Liberman, & Kuschel, ).…”
Section: Discussionsupporting
confidence: 82%
“…Second, previous research on regulatory fit found a similar asymmetry as we did, with fit effects emerging only for promotion focus/approach orientation (e.g., Fayant, Muller, Nurra, Alexopoulos, & Palluel‐Germain, ; Nussinson et al, ; Righetti et al, ; see also Woltin & Yzerbyt, ). This has been attributed to the greater focus on similarities rather than differences under promotion focus/approach orientation (Förster, ; Förster, Liberman, & Kuschel, ).…”
Section: Discussionsupporting
confidence: 82%
“…However, Woltin and Yzerbyt () recently documented the projection of general motivational orientations, namely, promotion and prevention regulatory foci. Our work suggests that this projection of general motivational orientations extends beyond dispositional regulatory foci to dispositional competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This is a non-intrusive and reliable methodology extensively used in the literature [4648]. Following this manipulation, we asked individuals to report their initial attraction to an attractive target and their romantic commitment.…”
Section: Studymentioning
confidence: 99%